FAKTOR PENDUKUNG KEBERHASILAN BADAN USAHA M ILIK KAMPUNG (BUMKAM) SEMINAI JAYA DI KAMPUNG SEMINAI KECAMATAN KERINCI KANAN KABUPATEN SIAK TAHUN 2021-2022 - Faizi, Iqbal Nur; ', Adlin, (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Village or Village-Owned Enterprises (BUMKAM) play a vital role in economic development in rural areas or villages. BUMKAM not only functions as the main driver of the local economy, but also as a tool for community empowerment, allowing village residents to actively participate in the economic process and create jobs. Research using the BUMDes Role Dimension Theory according to Seyadi, aims to identify factors that support the success or achievement of an institution, using a descriptive qualitative approach method. Data collection through interviews and documentation. This research allows for in-depth exploration of complex phenomena in the field. Data was collected through in-depth interviews with key stakeholders, direct observation of BUMKAM activities, as well as analysis of documents related to BUMKAM operations and performance. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this research reveal several main factors that contribute significantly to the success of BUMKAM Seminai Jaya. Visionary and inspirational leadership is proven to be able to direct the organization to achieve strategic goals. Quality human resources, both in terms of skills and commitment to the BUMKAM vision, are an important element in supporting optimal performance. In addition, a supportive external environment, including support from the village government, plays a role in creating a climate that supports business growth. Careful business planning, which includes comprehensive market analysis and measurable development strategies, provides a strong foundation for business sustainability. High community participation, which is reflected in active involvement in various BUMKAM activities, not only strengthens social ties but also increases the sense of shared ownership and responsibility for the success of BUMKAM. Keywords: BUMKAM, Success, Economic Empowerment, Seminai Village